Copolymer and method of manufacturing the same, copolymer mixture, dope resin composition, and resin molded article and method of manufacturing the same
Patent Information
- Application Number
- KR1020227006248
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2020-08-21
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2040-08-21
Smart Images

Figure 112022020708038-PCT00001 
Figure 112022020708038-PCT00002 
Figure 112022020708038-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a copolymer and a method for manufacturing the same, a copolymer mixture, a dope resin composition, and a resin molded article and a method for manufacturing the same. Background Technology
[0002] Copolymers containing constituent units derived from α-methylene lactone have excellent transparency, heat resistance, and optical isotropy, and are expected to be applied for optical applications. For example, Patent Document 1 describes that a film, etc., which is a molded body of a copolymer (resin) containing a predetermined constituent unit derived from α-methylene lactone, is suitable for use as an optical component. Prior art literature
[0003] Japanese Patent Publication No. 2008-179813 The problem to be solved
[0004] However, since copolymers containing constituent units derived from α-methylene lactone generally tend to have low solubility in solvents, polymerization is carried out in solvent-free or dimethyl sulfoxide (DMSO) solvents. However, in solvent-free polymerization, the heat of polymerization cannot be removed, and in DMSO solvent polymerization, the solvent itself decomposes upon heating, generating harmful substances, and also has explosive properties under certain conditions, which presents safety challenges and makes it unsuitable for industrialization. Furthermore, according to the inventors' investigation, it was found that when polymerization is carried out in DMSO solvent, the resulting copolymer containing constituent units derived from α-methylene lactone tends to become discolored and its transparency decreases.
[0005] Therefore, the present invention provides a method for manufacturing a copolymer comprising constituent units derived from α-methylene lactone by polymerization using a solvent, and the main objective is to provide a manufacturing method capable of improving the transparency of the obtained copolymer. means of solving the problem
[0006] The present invention provides a method for manufacturing a copolymer as described in [1] to [8] below, a copolymer as described in [9] to
[11] , a copolymer mixture as described in
[12] to
[14] , a dope resin composition as described in
[15] , a resin molded article as described in
[16] , and a method for manufacturing a resin molded article as described in
[17] and
[18] .
[0007] [1] A method for producing a copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, comprising a process of polymerizing monomers comprising α-methylene lactone and (meth)acrylate in the presence of a solvent, wherein the solvent is a solvent that satisfies either of the following conditions (A) or the following conditions (B).
[0008] Condition (A): At least one solvent selected from the group consisting of cyclic amides and cyclic esters.
[0009] Condition (B): A mixed solvent comprising a first solvent having a boiling point of less than 100°C and a second solvent having a boiling point of 100°C or higher, wherein the first solvent is at least one selected from the group consisting of ketones and alkyl chlorides, and the second solvent is at least one selected from the group consisting of cyclic ketones, cyclic esters, amides, and sulfoxides, and the mixed solvent has a boiling point of 70 to 120°C.
[0010] [2] A method for preparing a copolymer as described in [1], wherein the solvent is a solvent that satisfies condition (A).
[0011] [3] A method for preparing a copolymer as described in [1], wherein the solvent is a solvent that satisfies condition (B).
[0012] [4] A method for preparing a copolymer as described in [3], wherein the first solvent is acetone.
[0013] [5] A method for preparing a copolymer as described in [3] or [4], wherein the second solvent is a cyclic ketone.
[0014] [6] Method for preparing a copolymer described in [5], in which the cyclic ketone is cyclohexanone.
[0015] [7] A method for preparing a copolymer as described in [3] or [4], wherein the second solvent is at least one selected from the group consisting of cyclic esters, amides, and sulfoxides.
[0016] [8] A method for preparing a copolymer as described in [7], wherein the second solvent is at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, δ-valerolactone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N,N'-dimethylimidazolidinone and dimethyl sulfoxide.
[0017] [9] A copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, having an internal haze of less than 2.5% per 100 μm thickness when made into a film.
[0018]
[10] A copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, and having a weight average molecular weight of 200,000 or more and 1,000,000 or less.
[0019]
[11] L when using film * a * b * Internal b per 100㎛ thickness of the color system * A copolymer described in [9] or
[10] with a value of less than 1.6.
[0020]
[12] A copolymer mixture containing the copolymer described in any one of [9] to
[11] and at least one compound selected from the group consisting of cyclic amides, cyclic esters, and cyclic ketones.
[0021]
[13] A copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having alkyl groups having 1 to 6 carbon atoms, and a copolymer mixture comprising at least one compound selected from the group consisting of cyclic amides, cyclic esters, and cyclic ketones.
[0022]
[14] A copolymer mixture described in
[12] or
[13] , in which the content of the compound is 10 to 3000 mass ppm based on the total amount of the copolymer.
[0023]
[15] A dope resin composition containing a copolymer described in any one of [9] to
[11] and a dispersion medium, wherein the content of the copolymer is 5 mass% or more based on the total amount of the dope resin composition.
[0024]
[16] A resin molded body containing a copolymer described in any of [9] to
[11] or a copolymer mixture described in any of
[12] to
[14] .
[0025]
[17] A method for manufacturing a resin molded article, comprising the process of forming a resin composition containing a copolymer described in any of [9] to
[11] or a copolymer mixture described in any of
[12] to
[14] to obtain a resin molded article.
[0026]
[18] A method for manufacturing a resin molded body comprising a process of coating a dope resin composition described in
[15] and a process of removing a dispersion medium from the coated dope resin composition to obtain a resin molded body. Effects of the invention
[0027] According to the present invention, a method for producing a copolymer comprising constituent units derived from α-methylene lactone by polymerization using a solvent is provided, and a method for producing a copolymer capable of improving the transparency of the obtained copolymer is provided. A method for producing a copolymer according to some forms facilitates carrying out a polymerization reaction under reflux. Furthermore, according to the present invention, a copolymer obtained by such a method of production and a copolymer mixture containing said copolymer are provided. A copolymer mixture according to some forms tends to have excellent characteristics, such as a reduction in processing load on the formed film and strength of the formed film. Furthermore, according to the present invention, a dope resin composition using said copolymer or said copolymer mixture, a resin molded article, and a method for producing the same are provided. Specific details for implementing the invention
[0028] Embodiments of the present invention will be described in detail below. However, the present invention is not limited to the following embodiments.
[0029] In this specification, "resin (composition)" is a broader concept than "(co)polymer." The resin may be composed of, for example, one or two or more types of (co)polymers, and may, if necessary, contain additives such as antioxidants other than (co)polymers.
[0030] [Method for manufacturing copolymer]
[0031] A method for manufacturing a copolymer according to one embodiment is a method for manufacturing a copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms.
[0032] The constituent unit derived from α-methylene lactone is formed by the polymerization of α-methylene lactone in which a methylene group is bonded to a carbon at the α position. The specific structure of the constituent unit derived from α-methylene lactone is not particularly limited. The reduced water of the lactone is not particularly limited, but is preferably a five-membered ring (γ-lactone) or a six-membered ring (δ-lactone) in that the stability of the ring structure is high and, based on this high stability, a higher surface strength is obtained.
[0033] Specific examples of α-methylene lactones that are 5-membered or 6-membered rings are α-methylene-γ-butyrolactone and α-methylene-δ-valerolactone. These may have substituents.
[0034] The constituent unit derived from α-methylenelactone is preferably a constituent unit having the structure shown in the following formula (1).
[0035]
[0036] R in Equation (1) 1 to R 4 It is, independently of each other, a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms.
[0037] A constituent unit having the structure shown in formula (1) can be formed by the polymerization of a monomer containing α-methylene-γ-butyrolactone shown in the following formula (2).
[0038]
[0039] R in Equation (2) 1 to R 4 It is, independently of each other, a hydrogen atom or a hydrocarbon group having 1 to 18 carbon atoms.
[0040] The hydrocarbon group is an aliphatic hydrocarbon group or an aromatic hydrocarbon group. The aliphatic hydrocarbon group is, for example, an alkyl group. The number of carbon atoms in the alkyl group is preferably 1 to 10, more preferably 1 to 8. The alkyl group may be straight, branched, or cyclic. Examples of alkyl groups include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, a t-butyl group, an n-pentyl group, an n-hexyl group, a cyclopentyl group, a cyclohexyl group, etc.
[0041] Aromatic hydrocarbon groups are not particularly limited and may include, for example, heterocyclic structures. Examples of aromatic hydrocarbon groups include phenyl groups, tolyl groups, benzyl groups, etc.
[0042] R 1 to R 4 The atoms are, preferably independently of each other, hydrogen atoms or alkyl groups having 1 to 10 carbon atoms, more preferably all hydrogen atoms.
[0043] The content of constituent units derived from α-methylenelactone in the copolymer is preferably 5 to 40 mass%, more preferably 7.5 to 35 mass%, and even more preferably 10 to 30 mass%, from the perspective of further improving heat resistance, etc. In addition, the content of each constituent unit in the copolymer is determined by dissolving the copolymer in a medium solvent, 1 It can be obtained by measuring H-NMR and calculating the area ratio of the peaks corresponding to each constituent unit.
[0044] A constituent unit derived from (meth)acrylate alkyl having an alkyl group having 1 to 6 carbon atoms is formed by the polymerization of (meth)acrylate alkyl. Examples of alkyl groups having 1 to 6 carbon atoms in (meth)acrylate alkyl include methyl groups, ethyl groups, n-propyl groups, i-propyl groups, n-butyl groups, t-butyl groups, n-pentyl groups, n-hexyl groups, cyclopentyl groups, cyclohexyl groups, etc. These may be used individually or in combination of two or more types.
[0045] The number of carbon atoms in the alkyl group of the (meth)acrylate is preferably 1 to 3, more preferably 1 or 2, and even more preferably 1.
[0046] The number of carbon atoms in the alkyl group of the alkyl methacrylate is preferably 1 to 3, more preferably 1 or 2, and even more preferably 1.
[0047] The content of constituent units derived from (meth)acrylate in the copolymer is preferably 95 to 60 mass%, more preferably 92.5 to 65 mass%, and even more preferably 90 to 70 mass%, from the perspective of further improving heat resistance, transparency, etc.
[0048] The copolymer may include constituent units of monomers other than constituent units derived from α-methylene lactone and constituent units derived from (meth)acrylate alkyl having 1 to 6 carbon atoms. Specific examples thereof include constituent units derived from monomers such as (meth)acrylate benzyl, (meth)acrylate chloromethyl, (meth)acrylate 2-chloroethyl, styrene, vinyltoluene, α-methylstyrene, acrylonitrile, methyl vinyl ketone, ethylene, propylene, and vinyl acetate. These may be used individually or in combination of two or more.
[0049] The content of other constituent units in the copolymer is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less.
[0050] The method for preparing a copolymer according to the present embodiment comprises a process of polymerizing a monomer comprising α-methylene lactone and (meth)acrylate alkyl in the presence of a solvent. The solvent is a solvent that satisfies either of the following conditions (A) or (B).
[0051] Condition (A): At least one solvent selected from the group consisting of cyclic amides and cyclic esters.
[0052] Condition (B): A mixed solvent comprising a first solvent having a boiling point of less than 100°C and a second solvent having a boiling point of 100°C or higher, wherein the first solvent is at least one selected from the group consisting of ketones and alkyl chlorides, and the second solvent is at least one selected from the group consisting of cyclic ketones, cyclic esters, amides, and sulfoxides, and the mixed solvent has a boiling point of 70 to 120°C.
[0053] According to the method for manufacturing a copolymer according to the present embodiment, it is possible to improve the transparency of the obtained copolymer. Although the reason for this effect is not necessarily obvious, the inventors believe that the cause of discoloration (reduction in transparency) is the formation of a homopolymer of α-methylene lactone. The homopolymer is soluble in DMSO solvent alone, but tends not to be soluble or difficult to dissolve in a solvent satisfying condition (A) or a solvent satisfying condition (B). Therefore, it is believed that by polymerizing a monomer containing α-methylene lactone using a solvent satisfying condition (A) or a solvent satisfying condition (B), the formation of a homopolymer of α-methylene lactone is suppressed, thereby reducing the discoloration of the copolymer and improving transparency.
[0054] In addition, by using a solvent that satisfies condition (B), the method for manufacturing a copolymer according to the present embodiment makes it easier to perform a polymerization reaction under reflux when manufacturing a copolymer containing constituent units derived from α-methylene lactone, and enables polymerization to be carried out under reflux conditions at, for example, a general polymerization temperature (e.g., 70 to 120°C). When polymerization is carried out under reflux conditions, the heat of polymerization during polymerization can be controlled, and the polymerization temperature can be controlled near the boiling point, allowing the polymerization to proceed safely and stably. If the boiling point of the mixed solvent is 120°C or lower, it is advantageous in that it is easy to control the polymerization rate, suppress by-products, and prevent the polymerization temperature from becoming too high above the boiling point of the (meth)acrylate alkyl monomer. In addition, if the boiling point of the mixed solvent is 70°C or higher, it is advantageous in terms of productivity such as polymerization solution viscosity and polymerization rate.
[0055] The solvent indicated in condition (A) is at least one solvent selected from the group consisting of cyclic amides and cyclic esters, and may be a single solvent or a mixed solvent combining two or more types, but preferably a single solvent. The boiling point of the solvent (boiling point of the single solvent or boiling point of the mixed solvent) is preferably greater than 200°C and less than or equal to 300°C, in order to make it easier to control the content of the solvent (compound) in the copolymer mixture.
[0056] Examples of cyclic amides include N-methylpyrrolidone (NMP) and N,N'-dimethylimidazolidinone (DMI). Among these, NMP is preferably the cyclic amide due to its high versatility.
[0057] Examples of cyclic esters include γ-butyrolactone (GBL), γ-valerolactone, δ-valerolactone, etc. Among these, the cyclic ester is preferably GBL from the perspective of high versatility.
[0058] When using the solvent indicated in condition (A), the polymerization temperature and polymerization time vary depending on the type and ratio of monomers used, but the polymerization temperature is preferably 0 to 150°C, more preferably 50 to 150°C, and even more preferably 60 to 140°C. In addition, the polymerization time is preferably 0.5 to 20 hours, and more preferably 1 to 10 hours.
[0059] The solvent indicated in condition (B) is a mixed solvent comprising a first solvent having a boiling point of less than 100°C and a second solvent having a boiling point of 100°C or higher, wherein the first solvent is at least one selected from the group consisting of ketones and alkyl chlorides, and the second solvent is at least one selected from the group consisting of cyclic ketones, cyclic esters, amides, and sulfoxides, and the boiling point (of the mixed solvent) is 70 to 120°C.
[0060] The first solvent is a solvent having a boiling point of less than 100°C and is at least one solvent selected from the group consisting of ketones and alkyl chlorides. Examples of such first solvents include ketones such as acetone (ACE) and methyl ethyl ketone (MEK), and alkyl chlorides such as dichloromethane, chloroform, 1,2-dichloroethane, and 1,1-dichloroethane. The first solvent may be used alone or in combination of two or more types. Among these, the first solvent is preferably acetone.
[0061] The second solvent is a solvent having a boiling point of 100°C or higher, and is at least one solvent selected from the group consisting of cyclic ketones, cyclic esters, amides, and sulfoxides. Examples of such second solvents include cyclic ketones such as cyclohexanone (anone) and cyclopentanone; cyclic esters such as γ-butyrolactone (GBL), γ-valerolactone, and δ-valerolactone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone (NMP), and N,N'-dimethylimidazolidinone (DMI); and sulfoxides such as dimethyl sulfoxide. The second solvent may be used alone or in combination of two or more types. One embodiment of the second solvent is preferably a cyclic ketone, more preferably cyclohexanone. Another embodiment of the second solvent is preferably at least one selected from the group consisting of cyclic esters, amides, and sulfoxides, more preferably at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, δ-valerolactone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N,N'-dimethylimidazolidinone, and dimethyl sulfoxide.
[0062] The combination of the first solvent and the second solvent may be a combination of acetone and cyclohexanone. According to the inventors' investigation, while acetone and cyclohexanone each tend to have difficulty dissolving copolymers individually, it was found that they make it extremely easy to dissolve the aforementioned copolymer in a very specific way. Therefore, by using such a mixed solvent, it becomes easier to carry out the polymerization reaction under reflux, and it is possible to improve the transparency of the resulting copolymer.
[0063] The copolymer described above tends to be easily soluble in at least one solvent selected from the group consisting of cyclic esters, amides, and sulfoxides, having a boiling point of less than 100°C as the first solvent and a boiling point of 100°C or higher as the second solvent. Therefore, the combination of the first solvent and the second solvent may be a combination of an alkyl chloride having a boiling point of less than 100°C and at least one solvent selected from the group consisting of cyclic ketones, cyclic esters, amides, and sulfoxides, which has a boiling point of 100°C or higher, or a combination of at least one solvent selected from the group consisting of ketones and alkyl chlorides having a boiling point of less than 100°C and at least one solvent selected from the group consisting of cyclic esters, amides, and sulfoxides.
[0064] The boiling point of the mixed solvent is 70 to 120°C, preferably 75 to 115°C, and more preferably 80 to 110°C. Since the boiling point of the mixed solvent is within this range, it becomes easy to carry out the polymerization reaction under reflux. Furthermore, in this specification, the boiling point of the mixed solvent refers to a value measured by the method described in the examples.
[0065] The mixing ratio of the first solvent and the second solvent is not particularly limited and can be adjusted to any ratio as long as the boiling point of the mixed solvent is 70 to 120°C. By adjusting the first solvent and the second solvent to any ratio and adjusting the boiling point of the mixed solvent to a range of 70 to 120°C, it becomes easier to carry out the polymerization reaction under reflux and it becomes possible to improve the transparency of the resulting copolymer. For example, the mass ratio of the first solvent to the second solvent (mass of the first solvent / mass of the second solvent) is preferably 1 / 9 or more, more preferably 2 / 8 or more, preferably 9 / 1 or less, more preferably 8 / 2 or less, even more preferably 7 / 3 or less, particularly preferably 6 / 4 or less, and most preferably 5 / 5 or less.
[0066] When using the solvent indicated in condition (B), the polymerization temperature and polymerization time vary depending on the type and ratio of the monomer used, but the polymerization temperature is preferably 120°C or lower from the viewpoint that it is easy to control the polymerization rate, suppress by-products, and additionally the polymerization temperature does not become too high above the boiling point of the (meth)acrylate alkyl monomer, and is preferably 70°C or higher from the viewpoint of productivity such as polymerization solution viscosity and polymerization rate. The polymerization temperature is more preferably 75 to 115°C, and even more preferably 80 to 110°C. In addition, the polymerization time is preferably 0.5 to 20 hours, and more preferably 1 to 10 hours.
[0067] In the polymerization process, the method of introducing each monomer component (α-methylene lactone, (meth)acrylate alkyl, other monomers, etc.) into the reactor is not particularly limited, and examples include a method of introducing the entire amount of monomer before introducing the polymerization initiator, a method of continuously introducing the entire amount of monomer dropwise at the same time as introducing the polymerization initiator, a method of introducing a part of the monomer at first and introducing the remainder of the monomer dropwise after the polymerization begins, and a method of introducing by changing the content ratio of α-methylene lactone in the monomer composition introduced at first and the content ratio of α-methylene lactone in the monomer composition introduced after the polymerization begins.
[0068] When polymerizing monomers, a polymerization initiator may be added as needed. Examples of polymerization initiators include organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-t-butyl peroxide, lauroyl peroxide, benzoyl peroxide, t-butyl peroxyisopropyl carbonate, t-amyl peroxy-2-ethylhexanoate, and t-butyl peroxy-2-ethylhexanoate; and azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexane carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobis(2-methylpropionate). The content ratio of the polymerization initiator can be appropriately set according to the combination of monomers used, reaction conditions, etc., and is not particularly limited, but is preferably 10 to 10,000 mass ppm, more preferably 100 to 3,000 mass ppm, and even more preferably 300 to 2,000 mass ppm with respect to the total monomers.
[0069] When polymerizing monomers, a chain transfer agent may be added as needed. Examples of chain transfer agents include monofunctional thiol compounds such as n-dodecyl mercaptan and β-mercaptopropionic acid; difunctional thiol compounds such as biterminal mercapto-modified polysiloxanes; and branched-chain polyfunctional mercapto-modified polysiloxanes in which the branch chain is mercapto-modified. The content ratio of the chain transfer agent can be appropriately set according to the combination of monomers used, reaction conditions, etc., and is not particularly limited, but is preferably 10 to 10,000 mass ppm, more preferably 100 to 3,000 mass ppm, with respect to the total monomers.
[0070] When polymerizing monomers, in order to suppress the high viscosity of the reaction solution, it is desirable to control the concentration of the copolymer in the polymerization reaction mixture to 90 mass% or less, more preferably 70 mass% or less, and even more preferably 50 mass% or less. In addition, since productivity decreases if the concentration of the copolymer in the polymerization reaction mixture is too low, it is desirable to control the concentration of the polymer in the polymerization reaction mixture to 10 mass% or more, and more preferably 20 mass% or more.
[0071] The polymerization reaction mixture obtained through the polymerization process typically contains a solvent in addition to the copolymer that is the target product. Methods for separating the copolymer from the solvent are not particularly limited and include methods by reprecipitation, a degassing apparatus including a heat exchanger and a degassing tank, and a method of desolvating using an extruder equipped with a vent.
[0072] [Copolymer]
[0073] A copolymer according to one embodiment comprises a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, and has an internal haze of less than 2.5% per 100 μm thickness when formed into a film. The copolymer of this embodiment may be a copolymer obtained by the above manufacturing method. Since the above manufacturing method makes it possible to improve the transparency of the obtained copolymer, by using the said manufacturing method, the internal haze per 100 μm thickness when formed into a film and L when formed into a film * a * b * Internal b per 100㎛ thickness of the color system * It may be possible to set values, etc., within a predetermined range.
[0074] The copolymer has an internal haze of less than 2.5% per 100 μm thickness when formed into a film. The internal haze is preferably 2.0% or less, more preferably 1.5% or less, even more preferably 1.0% or less, and particularly preferably 0.8% or less. In addition, the internal haze per 100 μm thickness of the copolymer when formed into a film can be measured, for example, by the method described in the example. Furthermore, the temperature at which the copolymer is heat-press molded may be, for example, 200 to 270°C, and more specifically, 240°C.
[0075] A copolymer according to another embodiment comprises a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, and has a weight average molecular weight (Mw) of 200,000 or more and 1,000,000 or less. By using the copolymer of the present embodiment, it is possible to form a film with excellent transparency, heat resistance, and flexibility.
[0076] The copolymer is in a state that substantially does not contain the solvent used in the above manufacturing method. Here, "substantially does not contain" means that the solvent content is less than 10 mass ppm based on the total amount of the copolymer. In addition, the solvent content can be measured by using a film formed from the copolymer or a copolymer mixture, for example, by the method described in the example.
[0077] The copolymer is L when made into a film * a * b * Internal b per 100㎛ thickness of the color system * The value is preferably less than 1.6. The relevant internal b * The value is more preferably 1.2 or less, even more preferably 0.8 or less, particularly preferably 0.6 or less, and most preferably 0.4 or less. In addition, L when the copolymer is made into a film* a * b * Internal b per 100㎛ thickness of the color system * The value can be measured, for example, by the method described in the example. In addition, the temperature when heat-press molding the copolymer may be, for example, 200 to 270°C, and more specifically, 240°C.
[0078] The weight-average molecular weight (Mw) of the copolymer is preferably 100,000 or more, more preferably 150,000 or more, even more preferably 200,000 or more, particularly preferably 220,000 or more, and most preferably 240,000 or more. The weight-average molecular weight (Mw) of the copolymer is preferably 1,000,000 or less, more preferably 750,000 or less, and even more preferably 500,000 or less. If the Mw of the copolymer is within the above predetermined range, the flexibility of the film can be further improved. In addition, the Mw of the copolymer can be measured, for example, by the method described in the examples.
[0079] The number average molecular weight (Mn) of the copolymer is preferably 20,000 or more, more preferably 50,000 or more, and even more preferably 100,000 or more. The number average molecular weight (Mn) of the copolymer is preferably 500,000 or less, more preferably 400,000 or less, and even more preferably 300,000 or less. In addition, the Mn of the copolymer can be measured, for example, by the method described in the examples. In addition, the degree of dispersion (Mw / Mn) of the copolymer is preferably 3.0 or less, more preferably 2.8 or less, and even more preferably 2.5 or less.
[0080] The copolymer has a yellowness (YI) measured in accordance with the specifications of JIS Z 8729 when the copolymer is used in a 15% chloroform solution, which is preferably 5 or less, more preferably 3 or less, and even more preferably 1 or less. If the YI of the copolymer is within this range, a low-color resin molded article can be obtained.
[0081] The glass transition temperature (Tg) of the copolymer, measured in accordance with the specifications of JIS K 7121, is preferably 110°C or higher, more preferably 115°C or higher, and even more preferably 120°C or higher, from the perspective of further improving heat resistance, etc. The upper limit of the glass transition temperature of the copolymer is not particularly limited, but, for example, can be 160°C or lower.
[0082] The 5% weight loss temperature of the copolymer is preferably 280°C or higher, more preferably 290°C or higher, and even more preferably 300°C or higher, from the perspective of further improving heat resistance, etc. The upper limit of the 5% weight loss temperature of the copolymer is not particularly limited, but can be, for example, 400°C or lower. In addition, the 5% weight loss temperature can be measured by, for example, the method described in the examples.
[0083] [Copolymer Mixture]
[0084] A copolymer mixture according to one embodiment comprises a copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, and at least one compound selected from the group consisting of cyclic amides, cyclic esters, and cyclic ketones. One aspect of the copolymer mixture comprises the copolymer described above and at least one compound selected from the group consisting of cyclic amides, cyclic esters, and cyclic ketones.
[0085] At least one compound selected from the group consisting of cyclic amides, cyclic esters, and cyclic ketones may be used as a solvent as exemplified in the method for preparing the copolymer described above. The content of said compound is preferably 10 to 3000 ppm by mass based on the total amount of the copolymer. The content of said compound is more preferably 200 ppm by mass or more, even more preferably 300 ppm by mass or more, more preferably 2500 ppm by mass or less, and even more preferably 2000 ppm by mass or less based on the total amount of the copolymer. When the content of said compound is within this range, the processability of the resin, the reduction of the processing load on the formed film, and the strength of the formed film tend to be excellent. In addition, the content of the compound can be measured using a film formed from the copolymer or a copolymer mixture, for example, by the method described in the examples.
[0086] A copolymer mixture can be obtained in the method for manufacturing the copolymer described above by leaving the solvent (compound) in place so that the content of the compound is within a predetermined range when separating the copolymer from the solvent, and can also be obtained by adding the compound to the copolymer after isolation so that the content of the compound is within a predetermined range.
[0087] [Dope Resin Composition]
[0088] A dope resin composition according to one embodiment contains the copolymer described above and a dispersion medium. The dope resin composition can be suitably used for manufacturing a resin molded article.
[0089] Examples of dispersion media include, for instance, alkyl chloride solvents such as chloroform and dichloromethane; aromatic solvents such as toluene, xylene, and benzene; alcohol solvents such as methanol, ethanol, isopropanol, n-butanol, and 2-butanol; methyl cellosolve, ethyl cellosolve, butyl cellosolve, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, cyclohexanone, tetrahydrofuran, acetone, methyl ethyl ketone, ethyl acetate, diethyl ether, NMP, GBL, etc. These may be used individually or in combination of two or more. However, when two or more are used in combination, the solvent indicated in the above-described condition (B) shall be excluded.
[0090] Another embodiment of the dispersion medium is the solvent indicated in condition (B) described above. The boiling point of the mixed solvent (the solvent indicated in condition (B)) is preferably 70 to 120°C. The combination of the first solvent and the second solvent of the mixed solvent, the boiling point of the mixed solvent, the mixing ratio of the first solvent and the second solvent, etc., are the same as the combination of the first solvent and the second solvent, the boiling point of the mixed solvent, the mixing ratio of the first solvent and the second solvent described above. Therefore, redundant descriptions are omitted here. In addition, the first solvent may be further added to the mixed solvent described above. When the first solvent is further added to the mixed solvent described above, the boiling point of the dispersion medium is preferably 30 to 110°C, more preferably 40 to 100°C.
[0091] The copolymer content in the dope resin composition is 5 mass% or more, preferably 10 mass% or more, more preferably 15 mass% or more, and even more preferably 20 mass% or more, based on the total amount of the dope resin composition, from the perspective of efficiently manufacturing a resin molded article. The copolymer content is preferably 60 mass% or less, more preferably 50 mass% or less, and even more preferably 40 mass% or less, based on the total amount of the dope resin composition, from the perspective of ensuring fluidity for stable production with manufacturing equipment.
[0092] The dope resin composition may contain other polymers in the resin molded article described below. The content of other polymers is preferably 0 to 50 mass%, more preferably 0 to 40 mass%, even more preferably 0 to 30 weight%, particularly preferably 0 to 20 mass%, and most preferably 0 to 10 mass%, based on the total amount of the dope resin composition.
[0093] The dope resin composition may contain other additives in the resin molded article described below. The dope resin composition may contain one or more of the other additives. The content of the other additives is preferably 0 to 5 mass%, more preferably 0 to 2 mass%, and even more preferably 0 to 0.5 mass% based on the total amount of the dope resin composition.
[0094] The yellowness (YI) of the dope resin composition, measured in accordance with the standard of JIS Z 8729, is preferably 5 or less, more preferably 3 or less, and even more preferably 1 or less, from the perspective of obtaining a low-color resin molded article.
[0095] The viscosity of the dope resin composition at 25°C is preferably 0.001 Pa·s or more, more preferably 0.01 Pa·s or more, even more preferably 0.1 Pa·s or more, preferably 10 Pa·s or less, more preferably 5 Pa·s or less, and even more preferably 1 Pa·s or less, from the perspective of improving the productivity of the resin molded article. In addition, the viscosity at 25°C can be measured by, for example, the method described in the examples.
[0096] The haze of the dope resin composition, measured in accordance with the specifications of JIS K7136, is preferably 5 or less, more preferably 3 or less, and even more preferably 1 or less, from the perspective of obtaining a highly transparent resin molded article.
[0097] [Resin molded body and method of manufacturing the same]
[0098] A resin molded article according to one embodiment contains the copolymer described above or the copolymer mixture described above as a main component. A resin molded article according to this embodiment may be manufactured using a resin composition containing the copolymer described above or the copolymer mixture described above, or a dope resin composition containing the copolymer described above or the copolymer mixture described above.
[0099] The content of the copolymer or copolymer mixture is preferably 50 to 100 mass%, more preferably 60 to 100 mass%, even more preferably 70 to 100 weight%, particularly preferably 80 to 100 mass%, and most preferably 90 to 100 mass%, based on the total amount of the resin molded article. In the resin molded article, if the content of the copolymer or copolymer mixture is 50 mass% or more, a resin molded article with better transparency can be obtained.
[0100] The resin molded article may contain a polymer other than the copolymer described above (other polymers). Examples of other polymers include, for instance, olefin-based polymers such as polyethylene, polypropylene, ethylene-propylene copolymer, and poly(4-methyl-1-pentene); halogen-containing polymers such as vinyl chloride and vinyl chlorinated resin; acrylic-based polymers such as polymethyl methacrylate; styrene-based polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-acrylonitrile copolymer, and acrylonitrile-butadiene-styrene block copolymer; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyamides such as nylon 6, nylon 66, and nylon 610; polyacetal; polycarbonate; polyphenylene oxide; polyphenylene sulfide; polyetheretherketone; polysulfone; polyethersulfone; and polyoxybenzylene. Examples include polyamideimide; elastic organic fine particles such as polybutadiene-based rubber and acrylic-based rubber; and rubbery polymers such as ABS resin and ASA resin blended with polybutadiene-based rubber and acrylic-based rubber. The content of other polymers is preferably 0 to 50 mass%, more preferably 0 to 40 mass%, even more preferably 0 to 30 weight%, particularly preferably 0 to 20 mass%, and most preferably 0 to 10 mass%, based on the total amount of the resin molded body (resin composition).
[0101] The resin molded article may contain other additives. Examples of other additives include, for instance, antioxidants such as hindered phenolic, phosphorus-based, or sulfur-based compounds; stabilizers such as light stabilizers, weather stabilizers, or heat stabilizers; reinforcing materials such as glass fibers or carbon fibers; ultraviolet absorbers such as phenyl salicylate, (2,2'-hydroxy-5-methylphenyl)benzotriazole, or 2-hydroxybenzophenone; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, trialyl phosphate, or antimony oxide; antistatic agents such as anionic, cationic, or nonionic surfactants; coloring agents such as inorganic pigments, organic pigments, or dyes; organic fillers or inorganic fillers; resin modifiers; organic fillers or inorganic fillers; plasticizers; lubricants; antistatic agents; flame retardants; fluidizing agents; compatibilizers, etc. The resin molded article may contain one or more other additives. The content of the other additives is preferably 0 to 5 mass%, more preferably 0 to 2 mass%, and even more preferably 0 to 0.5 mass% based on the total amount of the resin molded article.
[0102] The resin molded article is preferably a film-shaped resin molded article or a sheet-shaped resin molded article. In addition, in this specification, a film-shaped resin molded article (film) means having a film thickness of less than 350 μm, and a sheet-shaped resin molded article (sheet) means having a film thickness of 350 μm or more.
[0103] One embodiment of a method for manufacturing a resin molded article comprises a process of obtaining a resin molded article by molding a resin composition containing the copolymer or the copolymer mixture described above. The method for molding the resin composition is not particularly limited, but may include, for example, conventionally known methods such as melt extrusion, calendering, and compression molding. Among these, the method for molding the resin composition is preferably melt extrusion.
[0104] The resin composition may contain, in addition to the copolymer or copolymer mixture described above, other polymers described above, other additives described above, etc., to suit the desired resin molded article. Furthermore, the content of the copolymer or copolymer mixture, other polymers, other additives, etc., in the resin composition may be the same as the content of each component exemplified in the resin molded article.
[0105] Specific examples of the melt extrusion method include, for instance, the T-die method and the inflation method. The molding temperature of the resin molded article is preferably 150 to 350°C, more preferably 200 to 300°C.
[0106] Another embodiment of the method for manufacturing a resin molded article comprises a process of coating the above-described dope resin composition and a process of removing a dispersion medium from the coated dope resin composition to obtain a resin molded article. The method for coating the dope resin composition is not particularly limited, but conventionally known methods such as the solution casting method (solution oscillation method) may be cited. For the solution casting method (solution oscillation method), devices such as a drum-type casting machine, a band-type casting machine, or a spin coater may be used.
[0107] The method for removing the dispersion medium from the dope resin composition is not particularly limited, but examples include heating the dope resin composition to volatilize the dispersion medium. The heating temperature can be appropriately set according to the dispersion medium used.
[0108] A resin molded body (film) in the form of a film can be made into a stretched film by stretching. The film is preferably a stretched film in that it has excellent flexibility and, in some cases, can impart a phase difference.
[0109] As a method for stretching the film, conventionally known stretching methods may be applied, such as uniaxial stretching with a free width and fixed width, and biaxial stretching with sequential biaxial stretching and simultaneous biaxial stretching. In that the bendability in any two orthogonal directions within the film plane is improved, the method for stretching the film is preferably biaxial stretching.
[0110] The stretching temperature when stretching the film is preferably near the glass transition temperature of the copolymer described above. More specifically, it is preferably (glass transition temperature - 30)°C to (glass transition temperature + 100)°C, more preferably (glass transition temperature - 20)°C to (glass transition temperature + 50)°C, and even more preferably (glass transition temperature - 10)°C to (glass transition temperature + 30)°C.
[0111] When stretching the film, the stretching ratio should be, for example, in the range of 1.05 to 10 times in both the longitudinal and transverse directions.
[0112] The film thickness of the film-shaped resin molded body (film) is preferably 1 μm or more and less than 350 μm, more preferably 10 μm or more and 300 μm or less. The film thickness of the sheet-shaped resin molded body (sheet) is preferably 350 μm or more and 10 mm or less, more preferably 350 μm or more and 5 mm or less.
[0113] When the resin molded article is a film, the total light transmittance of the film, measured by a method in accordance with JIS K7136, is preferably 85% or more, more preferably 88% or more, even more preferably 90% or more, and particularly preferably 92% or more. The total light transmittance is a standard for transparency, and if it is 85% or more, the transparency of the film can be considered sufficient.
[0114] When the resin molded article is a film, the elastic modulus of the film is preferably 4 GPa or more, more preferably 4.5 GPa or more, and even more preferably 5 GPa or more, from the perspective of further improving the strength of the film. The upper limit of the elastic modulus of the film is not particularly limited, but can be, for example, 15 GPa or less. In addition, the elastic modulus of the film can be measured by, for example, the method described in the examples.
[0115] When the resin molded body is a film, the Young's modulus of the film is preferably 4 GPa or more, more preferably 4.5 GPa or more, and even more preferably 5 GPa or more, from the perspective of further improving the strength of the film. The upper limit of the Young's modulus of the film is not particularly limited, but can be, for example, 15 GPa or less. In addition, the Young's modulus of the film can be measured by, for example, the method described in the examples.
[0116] In the case where the resin molded body is a film, the pencil hardness of the film is preferably H or higher, more preferably 2H or higher, and even more preferably 3H or higher in terms of further improving the strength of the film.
[0117] In the case where the resin molded body is a film, it is desirable that the film does not break in the folded portion even if the number of folds exceeds 100,000 times in a bending test (foldable test) in which the film is repeatedly bent into a U-shape and then unfolded under predetermined conditions. In addition, the predetermined conditions may be, for example, the conditions described in the examples.
[0118] The resin molded article of the present embodiment can be applied to various uses, and for example, it can be applied suitably for optical uses. Specific examples of uses include, for instance, light guide members, film applications, lenses (optical lenses, etc.), covers, and foam applications (e.g., cushioning materials, thermal insulation materials, vibration damping materials, soundproofing materials, sealing materials, packing materials, etc.).
[0119] The resin molded body of the present embodiment (particularly, a film-shaped resin molded body) can be suitably used for optical applications. Furthermore, since the resin molded body of the present embodiment (particularly, a film-shaped resin molded body) has excellent transparency, heat resistance, flexibility, and surface hardness, it can be suitably used for flexible display applications, and is particularly suitable for use as a cover window on the outermost surface. Specific examples of flexible displays include thin, bendable flexible type organic EL displays and smartphones capable of folding or winding. Additionally, since the film-shaped resin molded body has a low phase difference, it can also be used as a protective film for each layer of a flexible display. Furthermore, it is possible to manufacture a polarizing plate or a touch panel using the film-shaped resin molded body.
[0120] When applying a resin molded body (film) on a film as a cover window for a flexible display, it may be used as a laminate having other layers, such as a hard coating layer. In addition, the cover window for a flexible display formed from the film may be placed on the surface of a flexible display, for example, through an adhesive layer.
[0121] Examples
[0122] The present invention will be explained more specifically below with reference to examples, but the present invention is not limited by the examples. Furthermore, unless otherwise specifically stated, "parts" in the following description refers to "parts by mass." In addition, various physical properties were measured and evaluated as follows.
[0123] <Example A>
[0124] [Analysis of Polymerization Reaction Rate and Polymer Composition]
[0125] The reaction rate during the polymerization reaction and the content of specific monomer units in the copolymer were determined by measuring the amount of unreacted monomer in the obtained polymerization reaction solution using gas chromatography (manufactured by Shimadzu Seisakusho, device name: GC-2014).
[0126] [Weight Average Molecular Weight and Number Average Molecular Weight]
[0127] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the copolymer were determined by polystyrene conversion using gel permeation chromatography (GPC). The apparatus and measurement conditions used for the measurement are as follows.
[0128] System: Dosoje GPC System HLC-8220
[0129] Measurement side column configuration:
[0130] · Guard Column (Doso, TSKguardcolumn SuperHZ-L)
[0131] · Series connection of 2 separation columns (sticker, TSKgel SuperHZM-M)
[0132] Reference-side column composition:
[0133] · Reference Column (Dosoje, TSKgel SuperH-RC)
[0134] Developing solvent: Chloroform (Wako Junyaku High School product, Special Grade)
[0135] Developing solvent flow rate: 0.6 mL / min
[0136] Standard Sample: TSK Standard Polystyrene (Polystyrene, PS-Oligomer Kit)
[0137] Column temperature: 40℃
[0138] [ML content in copolymer]
[0139] The ML content in the copolymer (content of constituent units derived from α-methylenelactone) is, 1It was determined by H-NMR. Specifically, medium DMSO or medium chloroform was used as the medium solvent, and a nuclear magnetic resonance spectrometer (BRUKER AV300M) was used 1 H-NMR measurements were performed, and the obtained 1 It was obtained from the area ratio of the H-NMR profile.
[0140] [Glass Transition Temperature (Tg)]
[0141] The glass transition temperature of the copolymer was determined in accordance with the specifications of JIS K 7121. Specifically, using a differential scanning calorimeter (Rigaku, Thermo plus EVO DSC-8230), the temperature was evaluated by the starting point method from a DSC curve obtained by heating approximately 10 mg of a sample from room temperature to 200°C (heating rate 20°C / min) under a nitrogen gas atmosphere. α-alumina was used as the reference.
[0142] [5% weight loss temperature]
[0143] The 5% weight loss temperature of the copolymer was determined in accordance with the specifications of JIS K 7120. Specifically, using a differential differential thermal balance (Rigaku, Thermo plus2 Tg-8120), approximately 10 mg of a sample was heated from room temperature to 400°C at a rate of 10°C / min under a nitrogen gas atmosphere. The temperature was determined by measuring the point at which the mass of the sample decreased by 5% during the heating process.
[0144] [Film thickness]
[0145] The thickness of the film was determined using a digital micrometer (Mitutoyo).
[0146] [Total light transmittance of the film]
[0147] The total light transmittance of the film was determined in accordance with the standards of JIS K7361. Specifically, it was measured using a haze meter (Nippon Tenshoku Kogyo NDH-1001DP).
[0148] [Film Tensile Test (Measurement of Elastic Modulus)]
[0149] The stretched film was cut into a size of 90 mm × 20 mm to serve as a test specimen, and a tensile test was performed using an Autograph (manufactured by Shimadzu Seisakusho: AG-X) in accordance with JIS K7127 under an atmosphere of 25°C and 50% relative humidity. The conditions were set such that the tensile speed was 0.25 mm / min up to 0.5% deformation and 1 mm / min thereafter, the length of the chuck was 55 mm, and the spacing of the gauge for measurement was 25 mm. Three tests were performed at 25°C, and the average value was taken as the measurement value. Displacement was measured using a non-contact elongation gauge (manufactured by Shimadzu Seisakusho: TRViewX), and the elastic modulus was evaluated as a slope between 0.05% and 0.25% deformation.
[0150] [Young's modulus of film]
[0151] The Young's modulus of the film was evaluated for an extended film (thickness 4 μm) using a micro-hardness tester (Fischer Instruments, FischerScope HM-2000) in accordance with the method compliant with ISO-14577-1. The evaluation was performed with the unoriented film fixed to a glass substrate. The measurement conditions were set using a square pyramidal Vickers indenter (face angle a=136°), with a maximum test load of 3 mN; an application time of 20 seconds when the load is applied; a creep time of 5 seconds; an application time of 20 seconds when the load is reduced; and a measurement temperature of room temperature (25°C), and the value was obtained by averaging the values from three measurements.
[0152] [Pencil Hardness of Film]
[0153] The pencil hardness of the film was evaluated using a test pencil specified in JIS-S-6006 and a pencil scratch hardness tester No. 533 manufactured by Seiki Yasuda, in accordance with JIS K5600-5-4 (1999), under a load of 750g, and the hardness of the highest pencil that was not scratched was defined as the pencil hardness.
[0154] [Foldable Film Test]
[0155] A stretched film was cut to a size of 15 mm × 80 mm to serve as a test specimen, and was fixed with tape to a Tension-FreeFolding Clamshell-type (manufactured by Yuasa System Kiki, DMLHP-CS). Additionally, the test specimen was folded at the halfway point of its long side, and the folded state was set such that the distance between the two ends of the long side of the folded specimen was 5 mm and the radius of curvature of the folded portion of the specimen was 2.5 mm. Subsequently, under an environment of 25°C, the test was repeated 100,000 times at a rate of 30 folds per minute, with one fold defined as one open, flat state. After the test, the film in the folded portion was evaluated as "Good" if it did not break and as "Poor" if it did break.
[0156] (Example A1)
[0157] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 9 parts of methyl methacrylate (MMA), 0.75 parts of α-methylene-γ-butyrolactone (ML), and 10 parts of N-methylpyrrolidone (NMP) as a solvent were added, and the temperature was raised to 105°C while passing nitrogen through it. Then, 0.003 parts of t-amylperoxyisononanoate (prepared by Yoshitomi Alkema, Luperox (registered trademark) 570, hereinafter also referred to as "Initiator 570") were added as a polymerization initiator, and solution polymerization was carried out at 105-115°C for 6 hours while adding 0.005 parts of Initiator 570 diluted with 0.2 parts of NMP and 0.25 parts of ML at a constant rate over 2 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 98.8% and 99.3%, respectively. Next, the obtained polymerization reaction solution was vacuum dried (1 mmHg) at 240°C for 2 hours to obtain a white copolymer. The properties of the obtained copolymer are shown in Table 1. Next, the obtained copolymer was heat-press molded at 240°C to obtain an unoriented press film with a thickness of approximately 160 μm. Then, the obtained unoriented cast film was cut into 96 mm × 96 mm pieces, and using a sequential biaxial stretcher (Toyo Seiki Seisakusho, X6-S), sequential biaxial stretching was performed in the order of longitudinal direction (MD direction) and transverse direction (TD direction) at a stretching speed of 300% / min at a stretching temperature of 140°C (Tg+18°C) such that the stretching ratio was 2.0 times, respectively, and by cooling, an extended film with a thickness of 40 μm was obtained. The physical properties of the obtained extended film are shown in Table 1.
[0158]
[0159] <Test Example B, Example B and Comparative Example B>
[0160] [Polymerization reaction rate in static polymerization]
[0161] The polymerization reaction rate in static polymerization was determined simply by the amount of copolymer obtained after diluting the polymerization solution with chloroform, dropping it into methanol to extract the copolymer by redeposition, and drying the copolymer at 240°C for 1 hour.
[0162] [Analysis of Polymerization Reaction Rate and Copolymer Composition in Stirred Polymerization]
[0163] The reaction rate during the polymerization reaction in stirred polymerization and the content of specific monomer units in the copolymer were determined by measuring the amount of unreacted monomer in the obtained polymerization reaction solution using gas chromatography (manufactured by Shimadzu Seisakusho, device name: GC-2014).
[0164] [Weight Average Molecular Weight and Number Average Molecular Weight of Copolymers]
[0165] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the copolymer were determined in the same manner as the weight-average molecular weight and number-average molecular weight of the copolymer in <Example A>.
[0166] [ML content in copolymer]
[0167] The ML content in the copolymer (content of constituent units derived from α-methylene lactone) was determined in the same way as the ML content in the copolymer of <Example A>.
[0168] [Glass Transition Temperature (Tg) of Copolymer]
[0169] The glass transition temperature of the copolymer was determined in the same way as the glass transition temperature of the copolymer in <Example A>.
[0170] [5% weight loss temperature of copolymer]
[0171] The 5% weight loss temperature of the copolymer was determined in the same way as the 5% weight loss temperature of the copolymer in <Example A>.
[0172] [Internal haze of copolymer]
[0173] The internal haze of the copolymer was determined in accordance with the standard of JIS K7136. Specifically, an unoriented film obtained by heat-press molding the copolymer at 240°C and 40 MPa for 10 minutes was prepared, and using a haze meter (Nippon Tenshoku Kogyo, NDH-1001DP), 1,2,3,4-tetrahydronaphthalene (tetraline) was filled into a quartz cell with an optical path length of 10 mm, and the film was immersed in it to measure and calculate the internal haze value per 100 μm.
[0174] [Interior of the copolymer b * value]
[0175] An unoriented film obtained by heat-press molding a copolymer at 240°C and 40 MPa for 10 minutes was prepared, and using a spectrophotometer (Nippon Tenshoku Kogyo Colormeter ZE6000), 1,2,3,4-tetrahydronaphthalene (tetralin) was filled into a quartz cell with an optical path length of 10 mm, the film was immersed in it, and L * a * b * b per 100㎛ thickness of the color system * It was calculated as a value.
[0176] [Solvent (compound) content in copolymer or copolymer mixture]
[0177] The solvent (compound) content in the copolymer or copolymer mixture was determined by dissolving the copolymer or copolymer mixture in dimethylacetamide and then measuring it using gas chromatography (manufactured by Shimadzu Seisakusho, device name: GC-2014).
[0178] [Viscosity of Dope Resin Composition]
[0179] The viscosity of the dope resin composition was measured at 25°C using a BHII type viscometer (axe acid).
[0180] [Yellowness (YI) of Dope Resin Composition]
[0181] The yellowness (YI) of the dope resin composition was determined in accordance with the standards of JIS Z 8729. Specifically, it was measured using a quartz cell with an optical path length of 10 mm in the transmission mode of a spectrophotometer (Nippon Tenshoku Kogyo Colormeter ZE6000).
[0182] [Haze of Dope Resin Composition]
[0183] The haze of the dope resin composition was determined in accordance with the specifications of JIS K7136. Specifically, it was measured using a haze meter (Nippon Tenshoku Kogyo NDH-1001DP) and a quartz cell with an optical path length of 10 mm.
[0184] [Film thickness]
[0185] The thickness of the film was determined in the same way as the thickness of the film in <Example A>.
[0186] [Total light transmittance of the film]
[0187] The total light transmittance of the film was calculated in the same way as the total light transmittance of the film in <Example A>.
[0188] [Film Tensile Test (Measurement of Elastic Modulus)]
[0189] A tensile test (elastic modulus measurement) of the film was performed in the same manner as the tensile test of the film in <Example A>, and the elastic modulus was measured.
[0190] [Pencil Hardness of Film]
[0191] The pencil hardness of the film was determined in the same way as the pencil hardness of the film in <Example A>.
[0192] [Foldable Film Test]
[0193] A foldable test of the film was performed in the same manner as the foldable test of the film in <Example A>, and the presence or absence of breakage of the film in the folded portion after the test was evaluated in the same manner as in <Example A>.
[0194] [Film Phase Difference]
[0195] The in-plane phase difference Re and the thickness direction phase difference Rth of the stretched film for light of wavelength 589 nm were measured using an automatic birefringent meter (Oji Keisoku Kiki “KOBRA-WR”) under conditions of an incident angle of 40°. Specifically, the refractive index in the direction of the terminating axis within the film plane was denoted as nx, the refractive index in the direction of the leading axis within the film plane as ny, the refractive index in the thickness direction of the film as nz, and the film thickness as d, and the in-plane phase difference Re and the thickness direction phase difference Rth were each calculated from the following equation. In addition, in the following example, the film thickness d was set to 40 μm, and the in-plane phase difference Re and the thickness direction phase difference Rth were calculated.
[0196] In-plane phase difference Re=(nx-ny)×d
[0197] Phase difference in thickness direction Rth=[(nx+ny) / 2-nz]×d
[0198] Synthesis of copolymers by static polymerization
[0199] (Test Example B1)
[0200] 7 parts of methyl methacrylate (MMA), 3 parts of α-methylene-γ-butyrolactone (ML), 10 parts of N-methylpyrrolidone (NMP) as a solvent, and 0.03 parts of azobisisobutyronitrile (AIBN) as an initiator were added to a sealable reaction vessel. Nitrogen was bubbled into the vessel for 2 minutes to purify the nitrogen, after which the lid was closed to seal the vessel. Subsequently, the reaction vessel was immersed in an oil bath at 75°C for 2 hours to perform polymerization. After polymerization, the mixture was diluted with chloroform and added to methanol to perform reprecipitation, thereby extracting a white solid. Subsequently, the mixture was vacuum dried at 240°C for 1 hour to obtain approximately 6 parts of a white copolymer. The physical properties of the obtained copolymer are shown in Table 2.
[0201] (Test Example B2)
[0202] Polymerization, reprecipitation, and drying were performed in the same manner as in Test Example B1, except that the solvent was changed from NMP to γ-butyrolactone (GBL), and 6.5 parts of a white copolymer were obtained. The properties of the obtained copolymer are shown in Table 2.
[0203] (Test Example B3)
[0204] Polymerization, reprecipitation, and drying were performed in the same manner as in Test Example B1, except that the solvent was changed from NMP to dimethyl sulfoxide (DMSO), and six parts of a white copolymer were obtained. The properties of the obtained copolymer are shown in Table 2.
[0205] (Test Example B4)
[0206] Polymerization was carried out in the same manner as Test Example B1, except that the solvent was changed from NMP to toluene. However, the polymerization was terminated because a solid precipitated and solidified during the polymerization.
[0207] (Test Example B5)
[0208] Polymerization was carried out in the same manner as Test Example B1, except that solvents such as NMP were not used. However, the polymerization was terminated because a solid precipitated and solidified during the polymerization process.
[0209] From Test Examples B1 to B5, NMP, GBL, and DMSO with a polymerization reaction rate of 50% or more were judged to be good, and the following stirred polymerization was performed using these solvents.
[0210] Synthesis of Copolymers and Film Production by Stirred Polymerization
[0211] (Example B1-1)
[0212] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 8 parts of methyl methacrylate (MMA), 1.5 parts of α-methylene-γ-butyrolactone (ML), 0.005 parts of n-dodecyl mercaptan (nDM) as a chain transfer agent, and 10 parts of N-methylpyrrolidone (NMP) as a solvent were added, and the temperature was raised to 105°C while passing nitrogen through it. Then, 0.003 parts of t-amylperoxyisononanoate (prepared by Yoshitomi Alkema, Luperox (registered trademark) 570, hereinafter also referred to as "Initiator 570") were added as a polymerization initiator, along with 0.005 parts of Initiator 570 diluted with 0.2 parts of NMP and 0.5 parts of ML were added dropwise at a constant rate over 2 hours at 105 to 115°C. After dropwise addition, 4 parts of NMP were added, and solution stirring polymerization was further performed at 105 to 115°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 99.1% and 99.5%, respectively. The obtained polymerization reaction solution was vacuum dried at 240°C for 2 hours (133 Pa (1 mmHg)) to obtain a white copolymer. The physical properties of the obtained copolymer are shown in Table 3.
[0213] Next, the copolymer of Example B1-1 obtained was heat-press molded at 240°C to obtain an unoriented press film with a thickness of approximately 160 μm. The obtained unoriented film was cut into a size of 96 mm × 96 mm, and using a sequential biaxial stretcher (Toyo Seiki Seisakusho, X6-S), sequential biaxial stretching was performed in the order of longitudinal direction (MD direction) and transverse direction (TD direction) at a stretching speed of 300% / min at a stretching temperature of Tg+18°C (146°C) such that the stretching ratio was 2.0 times, respectively, and then cooled to obtain an oriented film with a thickness of 40 μm. The physical properties of the obtained oriented film are shown in Table 3.
[0214] (Example B1-2)
[0215] A copolymer and a stretched film with a thickness of 40 μm were obtained in the same manner as in Example B1-1, except that the solvent was changed from NMP to γ-butyrolactone (GBL). In addition, the conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 98.5% and 99.0%, respectively. The properties of the obtained copolymer and the properties of the stretched film are shown in Table 3.
[0216] (Example B1-3)
[0217] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 9 parts of MMA, 0.75 parts of ML, 0.005 parts of nDM, and 10 parts of GBL as a solvent were added, and the temperature was raised to 105°C while passing nitrogen through it. Then, 0.003 parts of initiator 570 were added, along with 0.005 parts of initiator 570 diluted with 0.2 parts of GBL and 0.25 parts of ML, which were added dropwise at a constant rate over 2 hours at 105 to 115°C. After the dropwise addition, 4 parts of GBL were added, and solution stirring polymerization was further performed at 105 to 115°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 98.4% and 99.2%, respectively. The obtained polymerization reaction solution was prepared in the same manner as in Example B1-1 to obtain a copolymer and a stretched film with a thickness of 40 μm. The properties of the obtained copolymer and the properties of the stretched film are shown in Table 3.
[0218] (Example B1-4)
[0219] A copolymer and a stretched film with a thickness of 40 μm were obtained in the same manner as in Examples B1-3, except that nDM was changed from 0.005 parts to 0.03 parts and GBL as a solvent was changed from 10 parts to 15 parts, and 4 parts of GBL added after dropwise addition were omitted. In addition, the conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 98.0% and 98.5%, respectively. The properties of the obtained copolymer and the properties of the stretched film are shown in Table 3.
[0220] (Example B1-5)
[0221] 7 parts of MMA, 2.2 parts of ML, and 10 parts of GBL as a solvent were added to a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and the temperature was raised to 105°C while passing nitrogen through it. Subsequently, 0.003 parts of initiator 570 were added, along with 0.005 parts of initiator 570 diluted with 0.2 parts of GBL and 0.8 parts of ML, which were added dropwise at a constant rate over 2 hours at 105 to 115°C. After the dropwise addition, 4 parts of GBL were added, and solution stirring polymerization was further performed at 105 to 115°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 99.1% and 99.2%, respectively. The obtained polymerization reaction solution was processed in the same manner as in Example B1-1 to obtain a copolymer and a stretched film with a thickness of 40 μm. The properties of the obtained copolymer and the properties of the stretched film are shown in Table 3.
[0222] (Comparative Example B1-1)
[0223] 7 parts of MMA, 3 parts of ML, and 10 parts of DMSO as a solvent were added to a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and the temperature was raised to 105°C while passing nitrogen through it. Subsequently, 0.02 parts of initiator 570 were added, and solution stirring polymerization was carried out at 105 to 115°C for 6 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 99.1% and 99.5%, respectively. The obtained polymerization reaction solution was processed in the same manner as in Example B1-1 to obtain a copolymer and a stretched film with a thickness of 40 μm. The physical properties of the obtained copolymer and the stretched film are shown in Table 3.
[0224] <Preparation of Dope Resin Composition and Production of Film>
[0225] (Example B2-1)
[0226] One part of the copolymer obtained in Example B1-2 and seven parts of dichloromethane as a dispersion medium were mixed, stirred by hand for 1 minute, and then stirred for 60 minutes to prepare a dope resin composition with a solid content of 12.5 mass%. The viscosity of the dope resin composition was 0.3 Pa·s, the YI was 0.9, and the haze was 0.3%. Upon visual inspection of the dope resin composition, it was found to be uniformly dispersed, and no change in the appearance of the dope resin composition was observed even after it was left to stand overnight.
[0227] Next, a dope resin composition was applied dropwise onto a PET film and spread using an applicator to a film thickness of 800 μm. Subsequently, each PET film was placed in a dryer and dried at 40°C for 30 minutes and at 60°C for 30 minutes, after which the coated film was peeled off from the PET. To prevent the obtained film from curling, wide angle clips were installed vertically and horizontally to hang the film from the dryer, and the film was dried at 100°C for 12 hours to obtain an unoriented cast film with a thickness of 160 μm. The obtained unoriented cast film was stretched using a sequential twin-axis stretcher in the same manner as in Example B1-1 to obtain an extended film with a thickness of 40 μm. The physical properties of the obtained extended film are shown in Table 3.
[0228]
[0229]
[0230] <Test Example C, Example C and Comparative Example C>
[0231] [Measurement of the boiling point of a mixed solvent]
[0232] 500 ml of mixed solvent was added to a 1 L separable flask equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and the temperature was raised while stirring and passing nitrogen through it, and the internal temperature when reflux was applied from the cooling tube was measured as the boiling point of the mixed solvent.
[0233] [Polymerization reaction rate in static polymerization]
[0234] The polymerization reaction rate in static polymerization was calculated simply in the same way as the polymerization reaction rate in static polymerization of <Test Example B, Example B, and Comparative Example B>.
[0235] [Analysis of Polymerization Reaction Rate and Copolymer Composition in Stirred Polymerization]
[0236] The reaction rate during the polymerization reaction and the content of specific monomer units in the copolymer in stirred polymerization were determined in the same manner as the reaction rate during the polymerization reaction and the content of specific monomer units in the copolymer in stirred polymerization of <Test Example B, Example B, and Comparative Example B>.
[0237] [Weight Average Molecular Weight and Number Average Molecular Weight of Copolymers]
[0238] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the copolymer were determined in the same manner as the weight-average molecular weight (Mw) and number-average molecular weight (Mn) of the copolymer in <Example A>.
[0239] [ML content in copolymer]
[0240] The ML content in the copolymer (content of constituent units derived from α-methylene lactone) was determined in the same way as the ML content in the copolymer of <Example A>.
[0241] [Glass Transition Temperature (Tg) of Copolymer]
[0242] The glass transition temperature of the copolymer was determined in the same way as the glass transition temperature of the copolymer in <Example A>.
[0243] [5% weight loss temperature of copolymer]
[0244] The 5% weight loss temperature of the copolymer was determined in the same way as the 5% weight loss temperature of the copolymer in <Example A>.
[0245] [Internal haze of copolymer]
[0246] The internal haze of the copolymer was determined in the same manner as the internal haze of the copolymers in <Test Example B, Example B, and Comparative Example B>.
[0247] [Interior of the copolymer b * value]
[0248] Interior b of the copolymer * The value is the internal b of the copolymer of <Test Example B, Example B and Comparative Example B>. * It was calculated in the same way as the value.
[0249] [Solvent (compound) content in copolymer]
[0250] The solvent (compound) content in the copolymer was determined in the same manner as the solvent (compound) content in the copolymers of <Test Example B, Example B, and Comparative Example B>.
[0251] [Viscosity of Dope Resin Composition]
[0252] The viscosity of the dope resin composition was determined in the same manner as the viscosity of the dope resin composition of <Test Example B, Example B, and Comparative Example B>.
[0253] [Yellowness (YI) of Dope Resin Composition]
[0254] The yellowness (YI) of the dope resin composition was determined in the same manner as the yellowness (YI) of the dope resin composition of <Test Example B, Example B, and Comparative Example B>.
[0255] [Haze of Dope Resin Composition]
[0256] The haze of the dope resin composition was determined in the same manner as the haze of the dope resin composition of <Test Example B, Example B, and Comparative Example B>.
[0257] [Film thickness]
[0258] The thickness of the film was determined in the same way as the thickness of the film in <Example A>.
[0259] [Total light transmittance of the film]
[0260] The total light transmittance of the film was calculated in the same way as the total light transmittance of the film in <Example A>.
[0261] [Film Tensile Test (Measurement of Elastic Modulus)]
[0262] A tensile test (elastic modulus measurement) of the film was performed in the same manner as the tensile test of the film in <Example A>, and the elastic modulus was measured.
[0263] [Pencil Hardness of Film]
[0264] The pencil hardness of the film was determined in the same way as the pencil hardness of the film in <Example A>.
[0265] [Foldable Film Test]
[0266] A foldable test of the film was performed in the same manner as the foldable test of the film in <Example A>, and the presence or absence of breakage of the film in the folded portion after the test was evaluated in the same manner as in <Example A>.
[0267] [Film Phase Difference]
[0268] The phase difference of the film was determined in the same way as the phase difference of the film in <Test Example B, Example B, and Comparative Example B>.
[0269] Synthesis of copolymers by static polymerization
[0270] (Test Example C1)
[0271] 7 parts of methyl methacrylate (MMA), 3 parts of α-methylene-γ-butyrolactone (ML), 10 parts of toluene (tol) as a solvent, and 0.03 parts of azobisisobutyronitrile (AIBN) as an initiator were added to a sealable reaction vessel. Nitrogen was then bubbled into the vessel for 2 minutes to purify the nitrogen, after which the lid was closed to seal the vessel. Subsequently, the reaction vessel was immersed in an oil bath at 75°C for 2 hours to carry out polymerization. However, the polymerization was terminated because a solid precipitated and solidified during the polymerization process. After polymerization, the mixture was diluted with chloroform and added to methanol to perform redeposition, thereby extracting a white solid.
[0272] (Test Example C2)
[0273] Polymerization was carried out in the same manner as Test Example C1, except that the solvent was changed from toluene to acetone (ACE). However, the polymerization was terminated because a solid precipitated and solidified during the polymerization.
[0274] (Test Example C3)
[0275] Polymerization was carried out in the same manner as Test Example C1, except that the solvent was changed from toluene to cyclohexanone (anone). However, the polymerization was terminated because a solid precipitated and solidified during the polymerization.
[0276] (Test Example C4)
[0277] Polymerization was carried out in the same manner as Test Example C1, except that the solvent was changed from toluene to a mixed solvent of acetone (ACE) and cyclohexanone (anone) (1:1 (mass ratio)). After polymerization, the mixture was diluted with chloroform, added to methanol to perform reprecipitation, and a white solid was extracted. Subsequently, the mixture was vacuum dried at 240°C for 1 hour to obtain approximately 6 parts of a white copolymer. The physical properties of the obtained copolymer are shown in Table 4.
[0278] From Test Examples C1 to C4, the mixed solvent of Test Example C4, in which no solid precipitated during polymerization, was determined to be good, and the following stirring polymerization was examined based on this mixed solvent.
[0279] Synthesis of Copolymers and Film Production by Stirred Polymerization
[0280] (Example C1-1)
[0281] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 7.5 parts of methyl methacrylate (MMA), 2 parts of α-methylene-γ-butyrolactone (ML), 0.005 parts of n-dodecyl mercaptan (nDM) as a chain transfer agent, and 10 parts of a mixed solvent of acetone (ACE) and cyclohexanone (anon) mixed in a 1:1 (mass ratio) as a solvent were added, and the temperature was raised to 70°C while passing nitrogen through it. Then, 0.004 parts of AIBN were added as a polymerization initiator, along with 0.011 parts of the initiator AIBN diluted with a mixed solvent of 0.2 parts of ACE and anon mixed in a 1:1 (mass ratio) and 0.5 parts of ML were added dropwise at a constant rate over 3 hours at 70 to 75°C. After dropwise addition, a mixed solvent of 4 parts of ACE and anone mixed in a 1:1 (mass ratio) was added, and solution stirring polymerization was further performed at 70 to 75°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 92.1% and 95.5%, respectively. The obtained polymerization reaction solution was vacuum dried (133 Pa (1 mmHg)) at 240°C for 2 hours to obtain a white copolymer. The physical properties of the obtained copolymer are shown in Table 5.
[0282] Next, the copolymer of Example C1-1 obtained was heat-press molded at 240°C to obtain an unoriented press film with a thickness of approximately 160 μm. The obtained unoriented film was cut into a size of 96 mm × 96 mm, and using a sequential biaxial stretcher (Toyo Seiki Seisakusho, X6-S), sequential biaxial stretching was performed in the order of longitudinal direction (MD direction) and transverse direction (TD direction) at a stretching speed of 300% / min at a stretching temperature of Tg+18°C (146°C) such that the stretching ratio was 2.0 times, respectively, and then cooled to obtain an oriented film with a thickness of 40 μm. The physical properties of the obtained oriented film are shown in Table 5.
[0283] (Example C1-2)
[0284] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 6 parts of methyl methacrylate (MMA), 3 parts of α-methylene-γ-butyrolactone (ML), 0.005 parts of n-dodecyl mercaptan (nDM) as a chain transfer agent, and 10 parts of a mixed solvent of acetone (ACE) and cyclohexanone (anone) mixed in a 3:7 (mass ratio) as a solvent were introduced, and the temperature was raised to 85°C while passing nitrogen through it. Subsequently, 0.004 parts of t-amylperoxy 2-ethylhexanoate (prepared by Yoshitomi Alkema, Luperox (registered trademark) 575, hereinafter also referred to as "Initiator 575") were added, along with 0.009 parts of Initiator 575 diluted with a mixed solvent of 0.2 parts ACE and anon mixed in a 3:7 (mass ratio) and 1 part of ML were added dropwise at a constant rate over 3 hours at 85 to 90°C. After adding, 4 parts of a mixed solvent of ACE and anon mixed in a 3:7 (mass ratio) were added, and solution stirring polymerization was further carried out at 85 to 90°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 93.1% and 95.5%, respectively. A white copolymer was obtained by vacuum drying the obtained polymerization reaction solution at 240°C for 2 hours (133 Pa (1 mmHg)). The properties of the obtained copolymer are shown in Table 5.
[0285] Next, the copolymer of Example C1-2 obtained was heat-press molded at 240°C to obtain an unoriented press film with a thickness of approximately 160 μm. The obtained unoriented film was cut into a size of 96 mm × 96 mm, and using a sequential biaxial stretcher (Toyo Seiki Seisakusho, X6-S), sequential biaxial stretching was performed in the order of longitudinal direction (MD direction) and transverse direction (TD direction) at a stretching speed of 300% / min at a stretching temperature of Tg+18°C (146°C) such that the stretching ratio was 2.0 times, respectively, and then cooled to obtain an oriented film with a thickness of 40 μm. The physical properties of the obtained oriented film are shown in Table 5.
[0286] (Example C1-3)
[0287] Six parts of methyl methacrylate (MMA), three parts of α-methylene-γ-butyrolactone (ML), and ten parts of a mixed solvent of acetone (ACE) and γ-butyrolactone (GBL) mixed in a 2:8 (mass ratio) were introduced into a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and the temperature was raised to 100°C while passing nitrogen through it. Subsequently, 0.004 parts of t-amylperoxyisononanoate (prepared by Yoshitomi Alkema, Luperox (registered trademark) 570, hereinafter also referred to as "Initiator 570") were added as a polymerization initiator, along with 0.009 parts of Initiator 570 diluted with a mixed solvent of 0.2 parts ACE and GBL mixed in a 2:8 (mass ratio) and 1 part of ML were added dropwise at a constant rate over 3 hours at 100 to 110°C. After adding, 4 parts of a mixed solvent of ACE and GBL mixed in a 2:8 (mass ratio) were added, and solution stirring polymerization was further carried out at 100 to 110°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 92.2% and 96.5%, respectively. A white copolymer was obtained by vacuum drying the obtained polymerization reaction solution at 240°C for 2 hours (133 Pa (1 mmHg)). The properties of the obtained copolymer are shown in Table 5.
[0288] Next, the copolymer of Example C1-3 obtained was heat-press molded at 240°C to obtain an unoriented press film with a thickness of approximately 160 μm. The obtained unoriented film was cut into a size of 96 mm × 96 mm, and using a sequential biaxial stretcher (Toyo Seiki Seisakusho, X6-S), sequential biaxial stretching was performed in the order of longitudinal direction (MD direction) and transverse direction (TD direction) at a stretching speed of 300% / min at a stretching temperature of Tg+18°C (146°C) such that the stretching ratio was 2.0 times, respectively, and then cooled to obtain an oriented film with a thickness of 40 μm. The physical properties of the obtained oriented film are shown in Table 5.
[0289] (Example C1-4)
[0290] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 5 parts of methyl methacrylate (MMA), 3.2 parts of α-methylene-γ-butyrolactone (ML), and 10 parts of a mixed solvent in which acetone (ACE) and N,N-dimethylacetamide (DMAc) were mixed in a 3:7 (mass ratio) as solvents were added, and the temperature was raised to 85°C while passing nitrogen through it. Then, 0.004 parts of initiator 575 were added, along with 0.009 parts of initiator 575 diluted with a mixed solvent in which 0.2 parts of ACE and DMAc were mixed in a 3:7 (mass ratio) and 1.8 parts of ML were added dropwise at a constant rate over 3 hours at 85 to 90°C. After dropwise addition, a mixed solvent of 4 parts ACE and DMAc mixed in a 3:7 (mass ratio) was added, and solution stirring polymerization was further performed at 85 to 90°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 90.2% and 95.5%, respectively. The obtained polymerization reaction solution was vacuum dried (133 Pa (1 mmHg)) at 240°C for 2 hours to obtain a white copolymer. The physical properties of the obtained copolymer are shown in Table 5.
[0291] Next, the copolymer of Example C1-4 obtained was heat-press molded at 240°C to obtain an unoriented press film with a thickness of approximately 160 μm. The obtained unoriented film was cut into a size of 96 mm × 96 mm, and using a sequential biaxial stretcher (Toyo Seiki Seisakusho, X6-S), sequential biaxial stretching was performed in the order of longitudinal direction (MD direction) and transverse direction (TD direction) at a stretching speed of 300% / min at a stretching temperature of Tg+18°C (146°C) such that the stretching ratio was 2.0 times, respectively, and then cooled to obtain an oriented film with a thickness of 40 μm. The physical properties of the obtained oriented film are shown in Table 5.
[0292] (Comparative Example 1-1)
[0293] 7 parts of MMA, 3 parts of ML, and 10 parts of DMSO as a solvent were added to a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and the temperature was raised to 105°C while passing nitrogen through it. Subsequently, 0.02 parts of initiator 570 were added, and solution stirring polymerization was carried out at 105 to 110°C for 6 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 99.1% and 99.5%, respectively. The obtained polymerization reaction solution was prepared in the same manner as in Example C1-1 to obtain a copolymer and a stretched film with a thickness of 40 μm. The physical properties of the obtained copolymer and the stretched film are shown in Table 5.
[0294] <Preparation of Dope Resin Composition and Production of Film>
[0295] (Example C2-1)
[0296] In a reactor equipped with a stirring device, a temperature sensor, a cooling tube, and a nitrogen inlet tube, 7.5 parts of methyl methacrylate (MMA), 2 parts of α-methylene-γ-butyrolactone (ML), 0.005 parts of n-dodecyl mercaptan (nDM) as a chain transfer agent, and 10 parts of a mixed solvent of acetone (ACE) and cyclohexanone (anon) mixed in a 3:7 (mass ratio) as a solvent were added, and the temperature was raised to 85°C while passing nitrogen through it. Then, along with the addition of 0.004 parts of initiator 575, 0.009 parts of initiator 575 diluted with a mixed solvent of 0.2 parts ACE and anon mixed in a 3:7 (mass ratio) and 0.5 parts of ML were added dropwise at a constant rate over 3 hours at 85 to 90°C. After dropwise addition, a mixed solvent of ACE and Anone mixed in a 3:7 (mass ratio) was added, and solution stirring polymerization was performed at 85 to 90°C for 4 hours. The conversion rates of MMA and ML calculated from the amount of unreacted monomer in the polymerization reaction solution were 93.1% and 97.5%, respectively. The obtained polymerization reaction solution was diluted with 55 parts of a mixed solvent of ACE and Anone mixed in a 3:7 (mass ratio) to prepare a dope resin composition with a copolymer content of 12.5 mass%. The dope resin composition was pressure-filtered using a 3 μm membrane filter. The physical properties of the dope resin composition are shown in Table 5. Upon visual inspection of the dope resin composition, it was found to be uniformly dispersed, and no change in the appearance of the dope resin composition was observed even after standing overnight.
[0297] Next, the dope resin composition of Example C2-1 was applied to a glass substrate and vacuum dried at 150°C for 2 hours to obtain an unoriented cast film with a thickness of 120 μm. The obtained unoriented cast film was stretched using a sequential twin-axis stretcher in the same manner as in Example C1-1 to obtain a stretched film with a thickness of 30 μm. The physical properties of the obtained stretched film are shown in Table 5.
[0298] (Example C2-2)
[0299] One part of the copolymer obtained in Example C1-2 and seven parts of dichloromethane as a dispersion medium were mixed, stirred by hand for one minute, and then stirred for 60 minutes to prepare a dope resin composition with a solid content of 12.5 mass%. The physical properties of the dope resin composition are shown in Table 5. Upon visual inspection of the dope resin composition, it was found to be uniformly dispersed, and no change in the appearance of the dope resin composition was observed even after it was left to stand overnight.
[0300] Next, the dope resin composition of Example C2-2 was applied dropwise onto a PET film and spread using an applicator to a film thickness of 800 μm. Subsequently, each PET film was placed in a dryer and dried at 40°C for 30 minutes and at 60°C for 30 minutes, after which the coated film was peeled off from the PET. To prevent the obtained film from curling, wide angle clips were installed at the top and bottom and the film was hung from the dryer. The film was then dried at 100°C for 12 hours to obtain an unoriented cast film with a thickness of 160 μm. The obtained unoriented cast film was stretched using a sequential twin-axis stretcher in the same manner as in Example C1-1 to obtain an extended film with a thickness of 40 μm. The physical properties of the obtained extended film are shown in Table 5.
[0301]
[0302]
Claims
Claim 1 A resin molded article comprising a copolymer comprising a constituent unit derived from α-methylene lactone and a constituent unit derived from (meth)acrylate having an alkyl group having 1 to 6 carbon atoms, wherein the weight average molecular weight of the copolymer is 220,000 or more and 1,000,000 or less, the glass transition temperature of the copolymer is 110°C or more and 160°C or less, the resin molded article is a stretched film, the internal haze per 100 μm thickness is 1.0% or less, and a test specimen cut to a size of 15 mm × 80 mm satisfies the following conditions, and is used as a film constituting a foldable or rollable flexible display. <Conditions> The test specimen is folded at the half-length position of the long side, and a folded state is set such that the distance between the two ends of the long side of the test specimen in the folded state is 5 mm and the radius of curvature of the folded portion of the test specimen is 2.5 mm, and the folded state is maintained in a flatly open state under an environment of 25°C. It does not break even when 100,000 bends are repeated at a speed of 30 bends per minute with one bend. Claim 2 In paragraph 1, L * a * b * Internal b per 100㎛ thickness of the color system * A resin molded body with a value of less than 1.
6. Claim 3 A flexible display comprising a resin molded body as described in paragraph 1 or 2. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 delete Claim 18 delete Claim 19 delete
Citation Information
Patent Citations
Planar thermoplastic resin molded article
JP2008179813A
tulipaline copolymer
JP2009517538A
